Exposure study to examine chemosensory effects of formaldehyde on hyposensitive and hypersensitive males - Müller, Jörg U.; Bruckner, Thomas; Triebig, Gerhard (International archives of occupational and environmental health, 2013)
ObjectiveMain objective of this study was to examine the chemosensory effects of formaldehyde on hyposensitive and hypersensitive males at concentrations relevant to the workplace. Attention focused on objective effects on and subjective symptoms of the mucous membranes of the eyes, the nose, the upper respiratory tract and olfactory function.MethodsForty-one male volunteers were exposed for 5 days (4 h per day) in a randomised schedule to the control condition (0 ppm) and to formaldehyde concentrations of 0.5 and 0.7 ppm and to 0.3 ppm with peak exposures of 0.6 ppm, and to 0.4 ppm with peak exposures of 0.8 ppm, respectively. Peak exposures were carried out four times a day over a 15-min period of time. Subjective pain perception induced by nasal application of carbon dioxide served as indicator for sensitivity to sensory nasal irritation. The following parameters were examined before and after exposure: subjective rating of symptoms and complaints (Swedish Performance Evaluation System), conjunctival redness, eye-blinking frequency, self-reported tear film break-up time and nasal flow rates. In addition, the influence of personality factors on the volunteer’s subjective scoring was examined (Positive And Negative Affect Schedule).ResultsFormaldehyde exposures to 0.7 ppm for 4 h and to 0.4 ppm for 4 h with peaks of 0.8 ppm for 15 min caused no significant sensory irritation of the measured conjunctival and nasal parameters. No differences between hypo- and hypersensitive subjects were seen. Nevertheless, statistically significant differences were noted for olfactory symptoms, especially for the ‘perception of impure air’. These subjective complaints were more pronounced in hypersensitive subjects.ConclusionsFormaldehyde concentrations of 0.7 ppm for 4 h and of 0.4 ppm for 4 h with peaks of 0.8 ppm for 15 min did not cause adverse effects related to irritation, and no differences between hypo- and hypersensitive subjects were observed.